Respuesta :

For this case we must solve the following equation:

[tex]\frac {5x} {2} + 3 = \frac {1} {7}[/tex]

We subtract 3 from both sides of the equation:

[tex]\frac {5x} {2} = \frac {1} {7} -3\\\frac {5x} {2} = \frac {1-21} {7}\\\frac {5x} {2} = \frac {-20} {7}\\\frac {5x} {2} = - \frac {20} {7}[/tex]

We multiply by 2 both sides of the equation:

[tex]5x = - \frac {40} {7}[/tex]

We divide by 5 on both sides of the equation:

[tex]x = - \frac {40} {7 * 5}\\x = - \frac {8} {7}[/tex]

Answer:

The solution is: [tex]x = - \frac {8} {7}[/tex]